CU ABDI RAHAYU DAN EFEKTIFITAS DIAKONIA GEREJA PAROKI MARGANINGSIH KALASA - Nugroho, Andreas (P3TK, Sanata Dharma University, 2015)
The Church has received the mission of Christ to carry out the works of Christ in the world. She continues the task of proclamation (kerygma), and celebrates the mystery of His presence (leitourgia) through the Word and the Liturgy, fellowship (koinonia) and service (diakonia) to others with the guidance of the Holy Spirit as a witness (martyria) to the world. From these elements, it is diakonia that can connect more closely to the act of Jesus who went around doing good (Acts 10:38). In this service, the Church gives more attention to the weak and poor people (trans. Kecil, Lemah, Miskin, Tersingkir, Difabel, abbr. KLMTD) to develop their life better. There are two forms of diakonia, namelydiakonia of charity (victim care; providing aids to the people in needs) and diakonia of empowerment (victim cause; helping people through empowerment). Thus, a movement such as Credit Union (CU) is one form of diakonia. This thesis was conducted to know how effective the Credit Union Abdi Rahayu realizediakonia of Marganingsih Parish, Kalasan, Yogyakarta. Subject of research is the service of CU Abdi Rahayu which is measured in several items, namely: financial education, saving reasons, the form of savings, easiness of borrowing, borrowing purposes, discipline of compulsory savings, assistance in using money and bad credit loans. The result of this research shows that the Credit Union Abdi Rahayu is able to realize some elements of Diakonia of Marganingsih Parish, Kalasan. This research also points act of solidarity among members as a tangible manifestation of love of neighbor.